Value co-creation in ecotourism: finding solutions in a digital era - Hernández-López, Laura (2018)
This study aims to identify the main actors in the ecotourism online value co-creation ecosystem. With the ever-increasing demand to which the ecotourism sector has been subject in recent years, there is a need for business models featuring interactive tools that allow ecotourists to participate and co-create their own experiences. Not only will ecotourism businesses and ecotourists participate in this process, but so too will several other stakeholders, becoming key actors in the co-creation of value. Ecotourism, being of a hedonic and experiential nature, requires strategies that are geared towards enjoyment of the joint value co-creation experience. With this finality, we present some factors, such as motivation, that are necessary for the ecotourist's value co-creation, as well as various other aspects that influence their behavior. Our expectation is that value co-creation will have a positive effect on the behavior and experiences of tourists when it comes to developing ecotourism products and services. Specifically, we expect that the implementation of a co-creation strategy will lead to greater satisfaction and loyalty. Accordingly, drawing on the existing literature, we present a theoretical proposal of the antecedents and consequents that affect and enable online value co-creation by ecotourists.